THE COVID-19 PANDEMIC AND THE ONLINIFICATION OF TEACHING AND LEARNING - Adrian NĂZNEAN (National Centre for Policy and Evaluation in Education, 2021)
Online education is of various types and can be defined in numerous ways. Over the last few decades, online education has gained popularity, but has also been regarded with reluctance and scepticism as to the benefits it may have. The COVID- 19 pandemic was declared on the 11th of March 2020 and forced many countries to impose lockdowns and restrictions. As such, several activities were shut down, schools and universities were closed, thus, the need for rapid solutions arose. Since the online environment was there for the taking, physical classrooms were virtualised overnight, homes became learning and teaching spaces for students and educators, whereas the latter were faced with adapting content and transferring it in order to suit its delivery via online platforms. With little to no experience in online education, educators sought to find ways to continue their work bringing emergency modifications. Although digital transformation is not a new phenomenon, the transit from physical classrooms to online ones has been and still is a rough learning curve for many educators. Apart from optimising digital technology to apply to education, another difficult task of any online teacher is to keep students motivated and involved, which can be achieved in different ways. This article discusses methods of content and course delivery, the technology-induced problems that online teaching implies, assessment, ethical behaviour in a virtual setting, and the risk of cheating in online examinations, as well as ways of preventing cheating. Nevertheless, the abrupt onlinification of education may lie at the basis of future exploration and research.